Metabolic regulation of T cell development - Zhang, Mengdi; Lin, Xiaoxi; Yang, Zhou; Li, Xia; Zhou, Zhiguang; Love, Paul E.; Huang, Jiaqi; Zhao, Bin (Frontiers in Immunology, 2022)
T cell development in the thymus is tightly controlled by complex regulatory mechanisms at multiple checkpoints. Currently, many studies have focused on the transcriptional and posttranslational control of the intrathymic journey of T-cell precursors. However, over the last few years, compelling evidence has highlighted cell metabolism as a critical regulator in this process. Different thymocyte subsets are directed by distinct metabolic pathways and signaling networks to match the specific functional requirements of the stage. Here, we epitomize these metabolic alterations during the development of a T cell and review several recent works that provide insights into equilibrating metabolic quiescence and activation programs. Ultimately, understanding the interplay between cellular metabolism and T cell developmental programs may offer an opportunity to selectively regulate T cell subset functions and to provide potential novel therapeutic approaches to modulate autoimmunity.